English Language Competence of Future Engineers: From Federal State Educational Standard to Tomsk Polytechnic University Best Practices; Mediterranean Journal of Social Sciences; Vol. 6, № 3 S1 - Goryanova L. N. Lyubov Nikolaevna (2015, 2015)
Title screen